2014
DOI: 10.1016/j.neuroimage.2013.10.063
|View full text |Cite
|
Sign up to set email alerts
|

Neural mechanisms supporting the extraction of general knowledge across episodic memories

Abstract: a b s t r a c t a r t i c l e i n f oGeneral knowledge acquisition entails the extraction of statistical regularities from the environment. At high levels of complexity, this may involve the extraction, and consolidation, of associative regularities across event memories. The underlying neural mechanisms would likely involve a hippocampo-neocortical dialog, as proposed previously for system-level consolidation. To test these hypotheses, we assessed possible differences in consolidation between associative memo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

3
47
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 35 publications
(50 citation statements)
references
References 81 publications
3
47
0
Order By: Relevance
“…This finding is consistent with Sweegers and colleagues (2014), the only analogous investigation of long-term retention of integrated knowledge conducted with adults to date. They found that directly learned, cross-episode relations were preferentially consolidated in memory as compared to isolated memories.…”
Section: Discussionsupporting
confidence: 89%
See 3 more Smart Citations
“…This finding is consistent with Sweegers and colleagues (2014), the only analogous investigation of long-term retention of integrated knowledge conducted with adults to date. They found that directly learned, cross-episode relations were preferentially consolidated in memory as compared to isolated memories.…”
Section: Discussionsupporting
confidence: 89%
“…In contrast, even when individuals become aware of the prototypical AB:BC paired associate structure, the arbitrary nature of the relations likely precludes deeper processing that could further enhance integration performance. Consistent with this interpretation, explicit awareness is also associated with integration in pattern-learning tasks in which individuals must extract subtle rules, such as how the spatial and non-spatial orientation of various fractals determine weather outcomes (Kumaran et al, 2009) or rules regarding face attributes repeatedly encountered at specific locations (Sweegers et al, 2014). Thus, it is possible that the nature of the stimuli might account for greater variability in explicit awareness of the relational structure relative to research utilizing more contrived, arbitrary items.…”
Section: Discussionmentioning
confidence: 87%
See 2 more Smart Citations
“…Because previous studies on similar topics (Kumaran et al, 2009; van Kesteren et al, 2010b, 2014; Sweegers et al, 2013) have identified a range of activation foci throughout the medial surface of PFC, we combined medial orbitofrontal and rostroanterior cingulate to create an MPFC ROI for each participant. ROIs were then aligned to each individual’s functional data using transformations applied in FLIRT, as described above.…”
Section: Methodsmentioning
confidence: 99%